Growth Pattern of Male and Female Kejobong Goats in Rural Areas - Purbowati, Endang; Rianto, Edy (Jurnal Ilmu-Ilmu Peternakan, 2024)
Growth is an important physiological activity in the animal that produces meat. This study aimed to investigate the growth rate of male and female Kejobong goats raised by farmers in Kejobong District, Purbalingga Regency, Central Java Province, Indonesia. The materials observed in this study were 43 female Kejobong goats aged 0–36 months and 34 male Kejobong goats aged 0–18 months, which were selected based on the available reliance sampling method. The relationship between the body weight (Y) and age (X) of the goats was analysed by cross-sectional comparison, with simple statistics and correlation regression. The body weights of male and female Kejobong goats aged 0–12 months were similar. However, after 12 months of age, the body weight of the males was greater than that of the females. The regression analysis and correlation between age and body weight in male and female Kejobong goats showed that the equation of the regression in the male goats was Y = - 0.040 X2 + 2.662 X + 1.105 and that in the female goats was Y = -0.019 X2 + 1.566 X + 4.665. The correlation coefficients (r) between age and body weight in male and female Kejobong goats were 0.97 and 0.90, respectively, while the coefficients of determination (r2) were 93.50% and 80.60%, respectively. It was concluded that the body weights of male and female Kejobong goats increased with the age of the goats. The relationship between age and body weight of Kejobong goats was very close